THE EFFECT OF ANIMATED VIDEO INTEGRATED WITH SCENARIO BASED LEARNING (SBL) ON SPEAKING PROFICIENCY OF HIGH SCHOOL STUDENTS - Ajizah, Aulya; Zulkarnain, Iskandar; Rahmawati, Wiki Tedi (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
This research investigates the influence of animated videos integrated with Scenario-Based Learning (SBL) on the speaking proficiency of Grade X students at SMA Negeri 17 Medan during the 2025/2026 academic year. Speaking proficiency is frequently recognized as a significant challenge for high school students, necessitating innovative pedagogical approaches to effectively foster student engagement and skill acquisition in modern classrooms. The study employed a quantitative true experimental design featuring a pre-test and post-test control group structure. The population comprised parallel Grade X classes, from which 30 students were meticulously selected through a random sampling technique. This sample was divided into an experimental group (n=15), taught using animated videos integrated with SBL, and a control group (n=15), receiving conventional instruction. Speaking proficiency was assessed through oral performance tests evaluating pronunciation, fluency, accuracy, and vocabulary.Data analysis conducted using a paired samples t-test revealed significant improvements across both groups. The experimental group’s mean score rose from 62.7 to 88.1, while the control group’s score increased from 59.4 to 76.1. Testing yielded a t-value of 7.491, exceeding the t-table value of 2.145 (df=14) with a significance value (p) of 0.000. These results indicate that the integration of animated videos with SBL exerts a statistically significant positive effect on students' speaking proficiency. The findings suggest that this integrated approach creates an engaging, interactive, and meaningful environment. By providing contextualized scenarios through visual media, students can better internalize linguistic components. Consequently, this instructional strategy is recommended as an effective tool for educators to enhance communicative competence.